Antibacterial Activity and an Upscaled Extraction Protocol for Terminalia ferdinandiana Exell. Leaves - Xu, Haokang; Cock, Ian Edwin (Pharmacognosy Communications)
Background: Terminalia ferdinandiana Exell. is an endemic Australian plant with a high anti-oxidant capacity. Liquid solvent extractions of T. ferdinandiana leaves are strong inhibitors of the growth of numerous bacterial pathogens. Despite these promising therapeutic properties, methods for the rapid extraction of large quantities of T. ferdinandiana leaves are lacking. This study aimed to develop a rapid supercritical extraction method to produce extracts which retain therapeutic properties and phytochemistry characteristics. Materials and Methods: Terminalia ferdinandiana leaves were extracted by both solvent maceration extraction and Supercritical fluid extraction (SCE). The extracts were tested for the ability to inhibit bacterial growth using the disc diffusion assay. The antibacterial potency was further quantified using liquid dilution MIC assays. Toxicity was evaluated using an Artemia franciscana nauplii bioassay and GC-MS headspace analysis was used to evaluate phytochemical similarity between the extracts. Results: Terminalia ferdinandiana leaf SCE displayed strong bacterial growth inhibitory activity against bacterial triggers of autoimmune inflammatory diseases, with efficacies similar to the smaller laboratory scale methanolic liquid extractions. The growth inhibition of the ethyl acetate and methanolic solvent extracts and the SCE were particularly noteworthy against P. mirabilis (MICs = 128, 227 and 208μg/mL respectively) and A. baylyi (MICs = 452, 780 and 104 μg/mL respectively). GC-MS analysis of the berry SCE revealed similar terpenoid components and similar abundances to those in methanolic solvent leaf extraction. Furthermore, all liquid extracts and the SCE were non-toxic in the Artemia franciscana toxicity assay. Conclusion: The T. ferdinandiana SCE retained the tested therapeutic properties, was non-toxic and had similar phytochemical profiles as the smaller scale liquid solvent extractions. Thus, SCE is a viable method of rapidly extracting large masses of T. ferdinandiana leaves to produce quality extracts that retain therapeutic properties.
Keywords: Kakadu plum; Combretaceae; Supercritical fluid extraction; Antibacterial activity; Autoimmune inflammatory disease; Extraction optimisation; Toxicity.